VD_FINDINFO Jug / 2014 / 276 vom 20. März 2014 - VD Tribunal cantonal (2014)
INFRACTIONS CONTRE LA VIE ET L'INTÉGRITÉ CORPORELLE, DOL ÉVENTUEL, FIXATION DE LA PEINE, TORT MORAL | 47 CO, 12 al. 2 CP, 19 al. 2 CP, 47 CP, 51 CP